The City Experiment : Rebuilding Greensburg, Kansas - Walker,Theo (NewYork Cambridge University, 2014)
After a tornado destroyed 95 of their town in 2007, the people of Greensburg decided to rebuild their town in a unique and exciting way. This reader details the ways Greensburg became green and how, by embracing the tragedy, Greensburg became a model community.
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Pre-Intermediate Level; Urban renewal